Effects of the COVID-19 Pandemic on Spinal Fusion Procedures for Spinal Infections in a Nationwide Hospital Network in Germany - Abduljawwad, Nehad; Pamnani, Sunisha; Stoffel, Michael; Kraft, Clayton N.; Hegewald, Aldemar A.; Dörre, Ralf; Heese, Oliver; Gerlach, Rüdiger; Rosahl, Steffen; Maier, Bernd; Burger, Ralf; Wutzler, Sebastian; Carl, Barbara; Ryang, Yu-Mi; Hau, Khanh Toan; Stein, Gregor; Gulow, Jens; Kuhlen, Ralf; Hohenstein, Sven; Bollmann, Andreas; Dengler, Julius (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background The full impact of the COVID-19 pandemic on surgical spine care is difficult to assess due to a lack in nationwide evidence from more recent phases of the pandemic. We aimed to describe changes in in-hospital processes associated with spinal fusion procedures in the treatment of spinal infections (SI) during different phases of the pandemic.Methods In this retrospective observational study, we examined the in-hospital prevalence and outcomes of spinal fusion procedures for SI (along with patient characteristics, rates of transfer to intensive care units, and mortality rates) during the first four waves of the pandemic compared with the corresponding prepandemic periods in 2019. We used administrative data from a nationwide network of 76 hospitals managing 7% of all in-hospital cases in Germany.Results We observed no significant change in the prevalence of SI fusion procedures during the pandemic, neither in total numbers (349 vs. 373) nor for each wave separately. On a patient level, we found no differences in age, sex, and the prevalence of paresis, and no relevant differences in associated comorbidities. The rate of mechanical ventilation did not change during any of the examined pandemic waves: it ranged between 9.5 and 18.6% during the pandemic and 3.1 and 16.0% during the corresponding prepandemic control periods. The rate of transfer to intensive care changed only during wave 4 (from 70.4 to 54.8%; p = 0.046) but not in any other pandemic phases. We observed no changes in in-hospital mortality rates (range: 2.9–9.7% vs. 6.2–11.3%) or in duration of hospital stay (range: 26.2–30.8 days vs. 20.8–29.2 days).Conclusions The main finding of our study is that within this nationwide network of spine care centers in Germany, the delivery of surgical treatment of SI by means of spinal fusion procedures was maintained throughout the first four waves of the pandemic. Furthermore, there were no relevant changes in patient demographics, in-hospital processes, and mortality rates.
Keywords: spinal infection; vertebral osteomyelitis; spondylodiskitis; spinal fusion; spinal osteosynthesis